Analisis Proses Manajemen Strategik Pada PT Campina Ice Cream - Margaretha, Cecilia; Ellitan, Lena (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Competitive advantage is the added value that a company has or an advantage that makes the company superior to other competitors in the product or service aspect so that it can attract attention when the target buyers are the same. Strategic management is very important to determine the decisions that must be made so that the company continues to survive and win over its competitors. This paper has several objectives as follows: (1). To find out the Vision, Mission, Goals and Strategy of PT Campina Ice Cream Industry. (2). To analyze the External and Internal Environment of PT Campina Ice Cream Industry. (3). To find out Strategy Implementation in Management aspects and other prominent aspects of PT Campina Ice Cream Industry. (4). To find out the Evaluation and Control of PT Campina Ice Cream Industry. Campina must continue to show that their company is running according to the company's vision, mission and goals. Campina also needs to continue to analyze the business environment, both external and internal, so that Campina can take advantage of existing opportunities and survive threats from outside the company as well as maximize the benefits of the company's strengths and overcome internal weaknesses. The many issues of management, operations, marketing, finance, research & development, and management information systems mean that successful strategy implementation is not guaranteed. Therefore, Campina needs to continue to carry out evaluation and control so that it can continue to survive and develop over a long period of time and in a sustainable manner (5). To analyze the Social Responsibility carried out by PT Campina Ice Cream Industry. (6). To analyze the strategy for achieving long-term sustainability (sustainability) of PT Campina Ice Cream Industry. Campina must continue to show that their company is running according to the company's vision, mission and goals. Campina also needs to continue to analyze the business environment, both external and internal, so that Campina can take advantage of existing opportunities and survive threats from outside the company as well as maximize the benefits of the company's strengths and overcome internal weaknesses. The many issues of management, operations, marketing, finance, research & development, and management information systems mean that successful strategy implementation is not guaranteed. Therefore, Campina needs to continue to carry out evaluation and control so that it can continue to survive and develop over a long period of time and in a sustainable manner.